VCDT: a method to stimulate creativity and wittiness among Administrative Science students / Noorayuni Rusli ... [et al.] - Rusli, Noorayuni; Muhamad Hakimi, Irwana Nooridayu; Ahmad Zawawi, Azlyn; Ismail, Junaida; Azizan, Intan Syahriza (UiTM Cawangan Kedah, 2021)
Debate is a common learning method used in the classroom at the secondary and tertiary levels. A lot has changed in the last several years, with learning approaches transitioning from traditional face-to-face to virtual methods. Virtual learning can be dull, unexciting, and monotonous if the instructors don't know how. Therefore, the virtual classroom debate tutorial (VCDT) approach is introduced to foster two-way participation during the online sessions. Even during the new norm, the practice of virtual classroom discussion improves self-confidence, critical thinking, communication skills and teamwork. The VCDT approach promotes a brilliant way of online discussion in which students are encouraged to speak spontaneously on the subject matters. The nature of debate activities helps sharpen rhetorical skills in a fast-paced virtual environment and enriching the students ability to solve problems. Therefore via VCDT exercises, students practice generating ideas under pressure within timeframe. This study employed 100 administrative science students as respondents, and the sampling technique used is purposive. The students participated in the VCDT session during a class tutorial, and a set of effectiveness scales was distributed after the session. SPSS was used to code the data collected from the respondents, and the students result reveal a good sign.